The Nature of Price Theory - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1969)
This article reviews "The Nature of Price Theory" by H.H. Liebhapsky.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z